Alleviating Poverty through the Use of Entrepreneurship Skill Acquisition in Kogi State, Nigeria - Adofu Ilemona; Ocheja Akoji; Abula Matthew (Aceh International Journal of Social Science, 2013)
Abstract - This study assessed the impact of entrepreneurship skill acquisition on poverty in Kogi State of Nigeria. The study made use of primary data collected with the aid of a well-structured questionnaire, which were administered by well-trained enumerator to beneficiaries of entrepreneurship acquisition skills randomly sampled from six Local Government Area of the state. The data collected through the questionnaire was analyzed using descriptive statistics like frequencies and percentages. The result shows that 65% of the respondents accepted that lack of entrepreneurship skills among youth is responsible for the high rate of poverty in Nigeria. The result also revealed that at least 60% of the people that benefitted from the skill acquisition programme can now afford the basic necessity of life. The study therefore recommended that since most of the people that benefited from the programme could afford the basic necessity of life, the government should begin to think of the way of developing the programme to the status of poverty eradication programme. Keywords : Entrepreneur; Vocation; Skill acquisition; Poverty; Alleviation; OptimumPaper Type : Research Paper